PENGEMBANGAN BAHAN BACAAN BERSTRUKTUR REFUTATION TEXT UNTUK MENGATASI MISKONSEPSI HUKUM NEWTON BAGI PESERTA DIDIK - Wulandari, Dewi; Maria S, Haratua Tiur; Arsyid, Syaiful B. (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
Misconceptions are students' understanding of a concept but this understanding is not in line with expert understanding. Misconceptions that occur in students can come from anywhere, including caused by textbooks and come from teachers who may also experience misconceptions without being aware of the teacher. The research method used is research and development using procedural examples. The procedural model is a descriptive model that explains the flow or procedural steps that must be followed to form a particular product. One of the products in the field of education is RD which can be in the form of an evaluation system, both process assessment and learning evaluation. This research produced a product in the form of reading material, Refutation text. In total, there was a decrease in the number of students who had misconceptions about the initial field test after being given Refutation text reading material by 76.18%. In total, there was a decrease in the number of students who experienced misconceptions about the main field trial after being given Refutation text reading material by 58.24%. and media at 79.95, the results of the quality test of reading material Refutation text on the content and presentation aspects of 0.74 are included in the high category. Meanwhile, the language aspect was 0.75 in the high category and the graphic aspect was 0.67 in the high category. Students' responses to the reading material of the Refutation text in the field test obtained an average percentage of 91.31%